Youths’ Adoption of Social Networking Sites: An Analysis Using TAM and TPB Model - Kapoor, Deepa (Gyan Management Journal, 2014)
The biggest gifts that mankind has got is technology and more so, it is the information technology that ;:as brought this world nearer. While growth, development and speed of progress have increased due to